A Layered P2‐ and O3‐Type Composite as a High‐Energy Cathode for Rechargeable Sodium‐Ion Batteries1. (1st April 2015) - Guo, Shaohua; Liu, Pan; Yu, Haijun; Zhu, Yanbei; Chen, Mingwei; Ishida, Masayoshi; Zhou, Haoshen
Abstract A layered composite with P2 and O3 integration is proposed toward a sodium‐ion battery with high energy density and long cycle life. The integration of P2 and O3 structures in this layered oxide is clearly characterized by XRD refinement, SAED and HAADF and ABF‐STEM at atomic resolution. The biphase synergy in this layered P2+O3 composite is well established during the electrochemical reaction. This layered composite can deliver a high reversible capacity with the largest energy density of 640 mAh g−1, and it also presents good capacity retention over 150 times of sodium extraction and insertion.